2015
DOI: 10.3892/ol.2015.3550
|View full text |Cite
|
Sign up to set email alerts
|

Adenoid cystic carcinoma of the larynx: A report of two cases

Abstract: Abstract. Laryngeal adenoid cystic carcinoma (ACC) is extremely rare, worldwide. From January 1994 to January 2014, all cases of laryngeal ACC that were diagnosed in the four largest hospitals in Hainan province, were reviewed. Only two such cases were identified. The first patient had a tumor in the subglottic region and the second patient, in the glottic region. The patient with subglottic ACC, who had experienced ongoing symptoms for 3 years, had previously been diagnosed with asthma, at a local hospital. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 17 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…According to the origin, laryngeal cancer is divided into three subtypes, supraglottic, glottic and subglottic, and airway obstruction are more frequently associated with subglottic tumors 3 . It makes a serious problem for airway management.…”
Section: Discussionmentioning
confidence: 99%
“…According to the origin, laryngeal cancer is divided into three subtypes, supraglottic, glottic and subglottic, and airway obstruction are more frequently associated with subglottic tumors 3 . It makes a serious problem for airway management.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with subglottic cancer show dyspnea, whereas common symptoms of glottis implications are dyspnea and a hoarse voice. Subglottic tumors are rare and associated with stridor and airway obstruction ( 12 ). In the present clinical case, an initial glottic and supraglottic lesion infiltrating the left true vocal cord and left ventricle caused hoarseness (due to vocal cord compromise) and dysphagia associated with ear pain for 1 year ( 10 ), and subsequently, the major extension of the lesion to the subglottic region resulted in dyspnea (due to airway obstruction) over the last month.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the metastasis rates of ACC located in the base of the tongue (19.2%), mobile tongue (17.6%) and mouth floor (15.3%) are higher than that of ACC of the larynx ( 15 ). In addition, clinical investigations have shown that the incidence of ACC with distant metastasis ranges from 35 to 50%, and leads to 5-year survival rates ranging from 12–17% following surgery ( 12 ). The lungs are the most common site of distant metastasis from ACC ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations